Gender Inequality in The Bahamas: Violence, Media, and Law - Storr, Juliette (Lexington Books, 2023)
This book examines sexual power dynamics, long-held patriarchal values, and other harmful attitudes toward women in The Bahamas and Caribbean through the lens of media and law. Though gender politics is pushing these societies toward inclusivity, Storr, adopting a phenomenological framework, argues that, as sites of both reinforcement and resistance to misogynistic norms, future progress must focus on deconstructing the inequitable social institutions underlying unhealthy gender relations.